Adoption of digitalised banking among generation Z in Malaysia - Lee, Choon Kit; Lee, Men Li; Lim, Wei Lun; Ong, Su Zhen; Wee, Guo Sheng (2023)
Digitalised banking refers to the application of technology for efficient execution of banking operations, encompassing electronic banking, internet banking, and online banking. The significant growth of digitalised banking and payment methods can be attributed to the utilization of digitalised assistants, radiofrequency devices, near-field communication-based technology, and wireless handsets. This research is aimed to investigate the adoption of Digitalised Banking among Generation Z in Malaysia. The study examines the adoption of Digitalised Banking among Generation Z in Malaysia by including the independent variables of perceived usefulness, perceived ease of use, social influence, security concern and trust. The target respondents included in this research project are all the Generation Z in Malaysia who were born from 1995-2012. The TAM used this research as it is a framework that predicts the adoption of early. TAM model can help to quantify the factors that affect generation Z's decision to accept or reject the INT. TAM can also explore the influences on generation Z's willingness to adopt digitalised banking. The data and information for this research were gathered via the self-administered survey questionnaire approach by using Google Form, which is a primary research method. Out of the 350 questionnaires that were collected, only 302 of them have been deemed suitable for use after going through a filtering process. We use Statistical Product and Service Solutions (SPSS) software to aid in our data analysis. This includes conducting tests such as discriminant validity, assessing the significance of variables, bootstrapping, as well as performing descriptive and inferential tests. The research project result concluded the independent variables towards the adoption of Digitalised Banking among Generation Z in Malaysia. Some limitations and suggestions are included in the study to provide better ideas for future researchers and even the government of Malaysia to enhance the intention of Malaysians in using digitalised banking products in Malaysia.